Simulation-Based Education in Pediatrics: The Febrile Neonate - Robert Dudas; David Cooke; Rosalyn Stewart; Eric Balighian; W. Golden; Michael Barone (Association of American Medical Colleges, 2014)
Abstract This simulation-based module on the febrile neonate requires 2-3 hours to deliver and includes interactive didactics supplemented by experiential learning utilizing partial-task trainers. Students are assigned prereading about the diagnostic considerations when evaluating a neonate with fever and are then quizzed during a large-group session using an audience response system to ensure their understanding of the material. Next, students are divided into small groups and rotate through stations to practice bladder catheterization, phlebotomy and intravenous placement, and lumbar puncture. Students are then presented simulated historical and laboratory data and asked to provide an assessment and plan. In order to measure the impact of the new curriculum on medical students in the course, each student completed surveys which were analyzed for the purposes of curriculum improvement. All 202 students who have completed this module agreed that they met the stated educational objectives, that their skills related to the topic were increased, and that the session was educationally valuable. Additionally, all students rated the session as very good or excellent. Narrative comments provided by students touched on the relevance of these skills to their role on the clerkship, the engaging nature of the sessions, and their increased confidence postsession.